Smoke and ashes : [large type] a novel - Mukherjee, Abir (Mukherjee, Abir. Sam Wyndham, 2019)
"Mukherjee makes the most of his setting, 1921 Calcutta, in his superior third mystery featuring the all-too-human Capt. Sam Wyndham, of the British Imperial Police, and his Indian assistant, Sgt. 'Surrender-Not' Banerjee. Mukherjee, who only gets better and better with each book, has established himself as a leading historical mystery writer." -- Publishers Weekly, starred India, 1921. Haunted by his memories of World War I, Captain Sam Wyndham is battling a serious addiction to opium that he must keep secret from his superiors in the Calcutta police force. When Sam is summoned to investigate a grisly murder, he is stunned at the sight of the body: he's seen this before. Last night, in a drug addled haze, he stumbled across a corpse with the same ritualistic injuries. It seems like there's a deranged killer on the loose. Unfortunately for Sam, the corpse was in an opium den--and revealing his presence there could cost him his career. With the aid of his quick-witted Indian Sergeant, Surrender-Not Banerjee, Sam must try to solve the two murders, all the while keeping his personal demons secret, before somebody else turns up dead.